Isoleucine Enhances Plant Resistance Against Botrytis cinerea via Jasmonate Signaling Pathway - Li, Yuwen; Li, Suhua; Du, Ran; Wang, Jiaojiao; Li, Haiou; Xie, Daoxin; Yan, Jianbin (Frontiers in Plant Science, 2021)
Amino acids are the building blocks of biomacromolecules in organisms, among which isoleucine (Ile) is the precursor of JA-Ile, an active molecule of phytohormone jasmonate (JA). JA is essential for diverse plant defense responses against biotic and abiotic stresses. Botrytis cinerea is a necrotrophic nutritional fungal pathogen that causes the second most severe plant fungal disease worldwide and infects more than 200 kinds of monocot and dicot plant species. In this study, we demonstrated that Ile application enhances plant resistance against B. cinerea in Arabidopsis, which is dependent on the JA receptor COI1 and the jasmonic acid-amido synthetase JAR1. The mutant lib with higher Ile content in leaves exhibits enhanced resistance to B. cinerea infection. Furthermore, we found that the exogenous Ile application moderately enhanced plant resistance to B. cinerea in various horticultural plant species, including lettuce, rose, and strawberry, suggesting a practical and effective strategy to control B. cinerea disease in agriculture. These results together showed that the increase of Ile could positively regulate the resistance of various plants to B. cinerea by enhancing JA signaling, which would offer potential applications for crop protection.